OPTIMIZING FOREIGN LANGUAGE TEACHING TO ENGINEERING MASTERS’ STUDENTS - Zelenin, H. (Problems of Engineer-Pedagogical Education, 2024)
The article analyses the actual problems of teaching foreign language professional communication in the master's program of an engineering higher education institution. The author emphasizes that to enhance foreign language teaching; we must adopt a competence-based approach and organize the learning process in a modular way. Additionally, incorporating information and communication technologies, including projectbased activities, is crucial for improving education in higher technical schools. By doing so, we can ensure that the content of teaching foreign language communication aligns perfectly with the demands of the labor market and professions. It also meets the expectations of master's students for excellence and professionalism. Using information and internet technologies during project activities not only helps master's students develop their foreign language skills, but also improves their research abilities. It fosters the cultivation of personal creative research knowledge and skills, as well as the ability to collaborate effectively within a team setting. Through this, the creative aptitude of each master's student can be effectively realized. This article highlights the invaluable expertise acquired by applying information and Internet technologies in foreign language classes at the Ukrainian Engineering Pedagogics Academy (Kharkiv) at the Master's level. Additionally, it explores how these technologies have greatly contributed to the independent and research work of Master's students. These educational activities have been found to greatly enhance the traditional approach to foreign language instruction, proving to be a highly efficient method. The activities provided offer a variety of cognitive, training, creative, and research exercises to enhance the foreign language skills of advanced students. These exercises involve addressing difficult and real-life situations. By employing such technologies, computer-based learning becomes increasingly prominent in foreign language education. As a result, the effectiveness, intensity, and individualization of language teaching improve significantly. Additionally, new forms of language instruction are introduced, even in unconventional learning environments. This approach strives to create a more immersive and dynamic language learning experience.